POSHAN’s abstract digest on maternal and child nutrition research - Issue 41 - Avula, Rasmi (International Food Policy Research Institute, 2021)
The 41st issue of POSHAN Abstract Digest brings to you yet again a tailored set of articles on malnutrition in India. This issue features a studies examining trends in nutrition outcomes, inequities associated with anthropometric failure, and role of WASH in addressing undernutrition. In addition, this issue also features articles on the intergenerational benefits of India’s national school feeding program, effect of women’s labor force participation on nutrition, and the role of maternal empowerment and paternal gender-equitable attitudes on stunting.